Algorithm Design and Testing For Environmental Adaptability in Virtual Reality - Wang, Yetong; Zheng, Bing; Xing, Kongduo (2025 International Conference on Electrical Drives, Power Electronics & Engineering (EDPEE), 2025)
As a cutting-edge field of modern technology, the application scope of virtual reality technology is constantly expanding. However, in complex dynamic environments, how to achieve real-time adaptation of the system to environmental changes has become one of the important challenges to improving the user experience. This paper focuses on the environmental adaptability in virtual reality and proposes an algorithm design method for environmental adaptability based on real-time data processing and dynamic optimization. The key technical requirements for environmental adaptability in virtual reality are analyzed. In view of the shortcomings of existing methods, an efficient environmental data collection, processing and adaptation algorithm is designed and implemented, focusing on solving the problem of balancing real-time and accuracy. By constructing test scenarios, the performance of the algorithm is comprehensively verified and analyzed. The algorithm in this paper is superior to traditional methods in terms of adaptation speed, stability and user experience. The research results provide an important reference for the development of virtual reality environmental adaptability technology and have shown great potential in multi-scenario applications.